Sobre la enseñabilidad de la administración. Algunas reflexiones preliminares (2021)
Actually many questions in relation to the present formation of the administrators exist and the formation system that the administration schools are using to professional them, nevertheless, is evident that in many ofthese establishments it has looked for to give to identiD! to the tasé of his integral formation and its expectations of professional formation in the discipline. However, it does not appear with the same clariy in relation to the demands of the socieD1, since, not always the professional in administration can give the suitable answers to the requirements of the community and in it confusion is generated between which it tries the society and the academy offers. Part of this racket can appear when not knowing suitable form the foundations of the enseñabilidad of the administrative discipline. It has been considerad by many actors of the formativa process, that the administration simply can be teachablefrom an instrumentalfundamentación, confusing more and more the administrativa knowledge with the administrativa practica. S upported in the thoughts ofdifferent authors who have elaborated studies in relation to the administrativa discipline, attempt to show how the education of the administration been has influenced basically by a modal of instrumental formation, which, has not facilitated a true epistemology development of the discipline.